The Dominant Sports Coaching Style Preferred by the Athletes from a State University in the Philippines - Abayari, Jenny Danica P.; Tilan, Karen M.; Aton, Armand G.; Reyes, Kristine Denise M. (Future Science / FSH-PH Publications, 2024)
This research explores the dominant sports coaching style preferred by athletes at Cavite State University Imus Campus in the Philippines. Drawing upon a descriptive research methodology, the study investigates athletes' preferences across various demographic factors and types of sports played. A total of 183 officially enrolled athletes participated in the study, providing valuable insights into their coaching preferences. The findings reveal a universal preference for democratic coaching styles (x̄= 4.69) among athletes, emphasizing collaboration, communication, and participatory decision-making. Regardless of age, sex, year level, or degree program, athletes consistently rated democratic coaching as their preferred style. However, variations and exceptions were observed across certain types of sports, highlighting the importance of tailored coaching approaches. An interesting finding emerged regarding archery, where the athlete's average ratings for all coaching styles—Democratic, Autocratic, and Laissez-Faire—were consistently rated as x̄=5.00, suggesting a preference for any coaching style by a single athlete. Moreover, exceptions were observed in specific sports. For instance, in Chess, an Autocratic coaching style was dominant, indicating a preference for a directive approach (x̄=4.91). Similarly, in Lawn Tennis, athletes showed dual preferences for both Democratic and Autocratic coaching styles. It is significant that coaches recognize and adapt to athletes' preferences to optimize engagement, motivation, and performance outcomes. Aligning the appropriate coaching style to the athletes’ preference, can enhance the overall athletic experience and contribute to the success and satisfaction of athletes in their sporting endeavors.